Modern Technologies in Improving the Quality of Teaching - Abdusalomovna, Haydarova Surayyo (International Journal of Psychosocial Rehabilitation, 2020)
It is known that today, almost all modern students come to the family with the knowledge and even the ability to use information and communication technologies before entering the secondary school. They are truly born in the information age and are growing up with modern communication devices, computers and other gadgets and their functions without understanding the world around them. In this case, the most important task of primary school teachers is to give students a basic understanding of these devices and the rules of their use. The role of the first teacher is important in building students' initial capacity to choose the right information for them from the world of information. Not only explanatory work in the process of teaching, education and upbringing, but also the level of ICT use in primary education, the introduction of ICT in the teaching of other key subjects in the curriculum is of great importance. In the process of improving the quality of lessons, teachers need to have the potential in the field of ICT to teach in accordance with modern requirements. This is one of the most important tasks of the continuing education system today. In general, the concept of potential in the field of information and communication technologies refers to a person's ICT literacy, that is, the ability to use it properly in everyday life and in professional activities.